1989
DOI: 10.1001/archotol.1989.01860260091021
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Neuromuscular Pedicles and Direct Nerve Implants in the Rabbit

Abstract: \s=b\Extension of neuromuscular pedicles and direct nerve implants was investigated in ten rabbits. All rabbits underwent facial nerve resection bilaterally. In five rabbits a neuromuscular pedicle, based on the ansa cervicalis nerve, was implanted into the denervated mentalis muscle unilaterally. On the opposite side, reinnervation was attempted using a neuromuscular pedicle with an interposed nerve graft. In the other five rabbits, reinnervation was attempted using a direct nerve implant on one side and a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Muscle force measurement is widely used to assess the mechanical function and contractile properties of a muscle [3541]. Our studies [28,3033] and others [23,25,42,43] have demonstrated that force measurement is a reliable technique in determining the degree of functional recovery of a reinnervated muscle. The denervated muscle is characterized by reduced muscle mass, decreased fiber size, increased connective tissue, and reduced metabolic capacity [44,45] which can be reversed by reinnervation [28,33,46].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Muscle force measurement is widely used to assess the mechanical function and contractile properties of a muscle [3541]. Our studies [28,3033] and others [23,25,42,43] have demonstrated that force measurement is a reliable technique in determining the degree of functional recovery of a reinnervated muscle. The denervated muscle is characterized by reduced muscle mass, decreased fiber size, increased connective tissue, and reduced metabolic capacity [44,45] which can be reversed by reinnervation [28,33,46].…”
Section: Discussionmentioning
confidence: 90%
“…The only reconstructive option to reinnervate that muscle is direct nerve implantation (i.e., muscular neurotization) [17,18] or nerve-muscle pedicle (NMP) transfer. The NMP technique has been used for laryngeal [1922] and facial reinnervation [2325]. However, controversy exists concerning the success rate of the NMP method.…”
Section: Introductionmentioning
confidence: 99%
“…In 1980's, Cummings and colleagues applied the NMP technique to facial reinnervation in animal experiments. 72-74 Clearly, this method has been employed primarily to treat paralyzed larynx and face. Up to date, many studies on the NMP reinnervation procedure have been reported in the literature over the past 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that NMP transfer resulted in functional outcomes similar to the DNI when evaluated by electromyography (EMG) and muscle tension. 72,74 NMP technique has been hampered by the fact that the muscle pedicle is harvested at the motor point (entry of the nerve into the muscle) where a nerve branch enters the muscle without considering the MEP band and nerve terminals. Some authors felt it probable that the small NMP might in fact contain cut ends of the nerve that acted in a fashion similar to that of a DNI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation